Auditor Quality, IFRS Adoption, and Stock Price Crash Risk: Korean Evidence. Issue 9 (1st September 2016) - Lim, Hyunil; Kang, Sang Koo; Kim, Haksoon
ABSTRACT: This paper investigates the relationship among auditor quality, International Financial Reporting Standard (IFRS) adoption and stock price crash risk. Using 657 unique listed companies spanning 2002–2014 in Korea, this study finds that stock price crash risk decreases, especially for firms using Big 4 auditors, after IFRS adoption in Korea. Stock price crash risk decreases for a firm included in Big 4 auditors, while it does not increase for a firm excluded from Big 4 auditors after IFRS adoption. Finally, this study finds that Big 4 auditor decreases stock price crash risk only when the firm size is above-median.